Strategies for Establishing Dependability between Two Qualitative Intrinsic Case Studies: A Reflexive Thematic Analysis. Issue 3 (August 2022) - Janis, Ilyana
Dependability (also known as consistency) is one of four criteria in rigor and trustworthiness in qualitative research. In this article, the process of establishing consistency is discussed through the lenses of constructivism and interpretivism, as the observed social reality is viewed as epistemologically counter-intuitive. Two strategies were used to establish consistency. First, method, source, and data triangulation were conducted concurrently to overcome differences in data collection methods from two qualitative intrinsic case studies. Second, code and meaning saturation were used in ATLAS.ti to identify similar meanings and interpretations despite different data collection methods. The findings showed that consistency can still be achieved, and similar meanings and interpretations can be established despite different data collection methods.